Protandry and female size-fecundity variation in the tropical butterfly Brassolis sophorae - Carvalho, M. C.; Queiroz, PCD; Ruszczyk, A. (Springer, 1998)
Protandry (the emergence of males before fe males) is currently explained either as a mating strategy to maximize number of matings in the males, or a way to minimize pre-reproductive mortality in females, Models of protandry have generally ignored variation in female quality (reproductive potential). We recorded the sex ratio, female body mass, wing length and potential fecundity (number and mass of eggs) of the tropical butterfly Brassolis sophorae through the emergence period. Temporal variation in female size and fecundity correlated with male potential for acquiring mates. Females from the end of the emergence period showed lower fecundity and size. Males emerging before and close to the median date of the female emergence period had greater mating opportunities. Males emerging either very early or late were penalized by few mating opportunities, or by encounters with small: low-quality females, respectively.
Keywords: protandry; size-fecundity variation; mate opportunity; tropical Lepidoptera; Brassolis sophorae